Ecodopplercardiografia em equinos submetidos à obstrução de cólon descendente - Toni, Maria Carolina [UNESP] (2014)
Colic syndrome is one of the most important problems of equine health, considering that damage to the intestinal barrier can lead to systemic inflammatory response syndrome, which can progress to sepsis. A significant consequence of sepsis is myocardial dysfunction. The aim of this study was to noninvasively evaluate the effects of endotoxemia and hence of sepsis related to colic syndrome using conventional two-dimensional echocardiography and tissue Doppler echocardiography on left ventricular indices, namely systolic and diastolic functions, in horses subjected to obstruction of the descending colon. The study was conducted at Governador Laudo Natel Veterinary Teaching Hospital - Faculdade de Ciências Agrárias e Veterinárias – Unesp – Jaboticabal, and was developed in parallel with a study that assessed inflammatory responses in horses after experimental obstruction of the descending colon. A single group was formed including eight adult mongrel horses with four females and four males, with average weight of 3705 kg and age of 101 years, were selected. The horses underwent laparotomy for obstruction of the descending colon by introducing a compression balloon. Echocardiographic variables were recorded in two stages, M0 representing baseline conventional and Tissue Doppler echocardiographic variables, and M48h representing the same parameters assessed 48 hours after intraluminal obstruction of the descending colon. Venous blood samples were collected for analysis and measurement of serum cytokine concentrations. Serum analysis revealed increased fibrinogen concentration and reduced platelet count. Doppler echocardiography showed decreased levels of VTi in M48h. Tissue Doppler allowed for determination of the occurrence of impaired systolic function indicated by the reduction of Sm in M48h. The change in the values of the ratio Em/Am as well as the increase of IVRT in M48h indicated impairment of diastolic function ...